PENINGKATAN PENGETAHUAN CARA MENGGOSOK GIGI DENGAN KEJADIAN KARIES GIGI MELALUI UPAYA PENYULUHAN (EDUKASI) KESEHATAN PADA MASYARAKAT DESA JUAI KECAMATAN JUAI KABUPATEN BALANGAN - M. Bahrul Ilmi; Erwin Ernadi (Universitas Islam kalimantan MAB, 2017)
One cause is the high patient dental caries is the pattern of brushing your teeth is still anything wrong, lack of awareness in the patient undergoing treatment and healing process includes went to health services for prevention. The purpose of this service activities is to increase public knowledge about the prevention and treatment of dental caries disease. The method is performed in service activities is a lecture / extension, namely the provision of information (education) about brushing teeth and dental caries. Targets in community service activities are 15-60 years of age because this age group is the age group most vulnerable to suffer from dental caries so that they can explain to their children or relatives. These service activities will be conducted from November 2016 to January 2017. Hopefully with this service activities, more and more people know about the information how to brush their teeth so they can reduce or avoid the disease dental caries.